2016
DOI: 10.21037/jtd.2016.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of off-pump coronary artery bypass grafting on survival: current best available evidence

Abstract: Abstract:The superiority of either off-pump (OPCAB) or on-pump (ONCAB) coronary artery bypass grafting (CABG) remains unclear despite a large body of literature evidence comparing the two approaches.The potential advantages of avoiding cardiopulmonary bypass (CPB), minimizing aortic manipulation and maintaining pulsatile flow may be associated with reduced inflammatory responses and embolic events.Numerous studies compared OPCAB with ONCAB and the cumulative data have been presented in metaanalyses of both ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This meta-analysis concentrated on prospective RCTs; however there been other large retrospective studies that have investigated long term survival. On the whole, these studies have shown no difference in mortality between off pump and on pump CABG [18]. In the 2 exceptions long-term survival rates were significantly better in the on pump group.…”
Section: Discussionmentioning
confidence: 80%
“…This meta-analysis concentrated on prospective RCTs; however there been other large retrospective studies that have investigated long term survival. On the whole, these studies have shown no difference in mortality between off pump and on pump CABG [18]. In the 2 exceptions long-term survival rates were significantly better in the on pump group.…”
Section: Discussionmentioning
confidence: 80%
“…2 For decades, the heart is typically arrested with cardioplegia undergoing cardiopulmonary bypass (CPB) to ensure a bloodless surgical field for CABG. 3 However, this conventional on-pump CABG (ONCAB) is often associated with potentially negative effects, including activation of systemic inflammatory responses, excessive haemodilution, haemodynamic instability and risk of air embolism or atherosclerotic debris. These adverse events often lead to subsequent multiorgan dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Off-pump surgical revascularization of complex coronary artery disease has gained worldwide attention [ 2 , 3 , 4 ]. The major advantage of off-pump coronary artery bypass grafting (OPCAB) consists in the avoidance of non-physiological blood flow and minimization of the risk of complications related to inflammatory response.…”
Section: Introductionmentioning
confidence: 99%